On strategies of teaching a foreign language in the context of inclusive education - Nina S. Evstropova; Elena V. Rakova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Currently, the so-called "inclusive education", which acts as the only internationally recognized tool to enforce everyone’s right to education, is becoming a very important part of the education system reform in Russia. Inclusive education, as part of the educational policy of many countries - members of the international organization UNESCO, is seen as a dynamic approach, which presupposes a positive attitude to the diversity of students as well as perception of individual characteristics not as a problem, but as an opportunity to enrich the learning process. High quality education for all students is an essential requirement of educational inclusion applied in international practice. Nowadays, in modern practice there is already some positive experience in implementation of inclusion in the process of teaching foreign languages at higher educational institutions. Basic knowledge of a foreign language helps such students to socialize, to become more independent and to avoid difficulties when communicating and interacting in the educational environment. Thus, the main task of inclusive education - socialization of children with disabilities is implemented. Moreover, practice of this type is based on the idea of accepting the individuality of each student. That is why, the process should be organized in such way to meet the needs of students with disabilities. Therefore, this paper is aimed at studying the strategies of involving students with disabilities in the educational process and improving their results when teaching a foreign language. The authors focus on Internet resources and communication strategies used in interaction with students in the framework of inclusive education.